The Effect of Land Property Rights on China’s Rural-Urban Migration - Gu, Yuankai (Transactions on Economics, Business and Management Research, 2024)
China’s rural land system, a fundamental economic system essential for rural construction, agricultural development, and farmers’ income in China, is currently being reformed through the Three Rights Division (TRD) mechanism to promote transformation of land management and improve the security of land contract rights. This paper examines the effects of rural land systems in China on migration, considering market mechanisms, such as land rentals, and government mechanisms, such as land expropriation. Analysis using the Probit model reveals why renting land has had a constructive effect on migration in China through the TRD reform that promotes land security and encourages migration through both market and government mechanisms. Moreover, the TRD boosts urbanization because industry structure upgrades assist China in avoiding possible middle-income traps and Lewis turning points, thereby fostering overall economic growth.